Associations of depression and regional brain structure across the adult lifespan: Pooled analyses of six population-based and two clinical cohort studies in the European Lifebrain consortium - Binnewies, J; Nawijn, L; Brandmaier, AM; Baaré, WFC; Bartrés-Faz, D; Drevon, CA; Düzel, S; Fjell, AM; Han, LKM; Knights, E; Lindenberger, U; Milaneschi, Y; et al. (Elsevier, 2022)
Objective Major depressive disorder has been associated with lower prefrontal thickness and hippocampal volume, but it is unknown whether this association also holds for depressive symptoms in the general population. We investigated associations of depressive symptoms and depression status with brain structures across population-based and patient-control cohorts, and explored whether these associations are similar over the lifespan and across sexes.